2001
DOI: 10.1084/jem.193.9.1027
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Inducible Factor 1–Dependent Induction of Intestinal Trefoil Factor Protects Barrier Function during Hypoxia

Abstract: Mucosal organs such as the intestine are supported by a rich and complex underlying vasculature. For this reason, the intestine, and particularly barrier-protective epithelial cells, are susceptible to damage related to diminished blood flow and concomitant tissue hypoxia. We sought to identify compensatory mechanisms that protect epithelial barrier during episodes of intestinal hypoxia. Initial studies examining T84 colonic epithelial cells revealed that barrier function is uniquely resistant to changes elici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
386
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 399 publications
(406 citation statements)
references
References 43 publications
17
386
1
2
Order By: Relevance
“…57 Previous studies showed that adaptive hypoxia protects the intestinal epithelial barrier integrity via transcriptional regulation of hypoxiainducible factor 1. [22][23][24] Further investigation of the molecular Figure 9 Depletion of blood neutrophils blocked the hypoxic preconditioning (HPC) protection against ischemia/reperfusion (I/R) injury. Rats exposed to HPC were administered anti-PMN or isotype antibodies, and then subjected to mesenteric I/R challenge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…57 Previous studies showed that adaptive hypoxia protects the intestinal epithelial barrier integrity via transcriptional regulation of hypoxiainducible factor 1. [22][23][24] Further investigation of the molecular Figure 9 Depletion of blood neutrophils blocked the hypoxic preconditioning (HPC) protection against ischemia/reperfusion (I/R) injury. Rats exposed to HPC were administered anti-PMN or isotype antibodies, and then subjected to mesenteric I/R challenge.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][21] Other reports have indicated that adaptive hypoxia protects the intestinal epithelial barrier integrity via transcriptional regulation of hypoxia-inducible factor 1 in experimental colitis models. [22][23][24] It remains unclear whether HPC attenuates mesenteric I/R-induced intestinal mucosal injury and BT.…”
mentioning
confidence: 99%
“…A number of studies have revealed that HIF elicits a barrier protective program in the intestine [17][18][19][20]. While originally guided by microarray analysis of differentially expressed messenger ribonucleic acid (mRNA) in cultured epithelial cells subjected to hypoxia, these studies have proven robust in a number of animal models of inflammation.…”
Section: Hif Is Protective For Mucosal Inflammationmentioning
confidence: 99%
“…Third, HIF-dependent epithelial barrier-protective pathways driven by hypoxia tend to be more "nonclassical" regulators of barrier function. Rather than classic junctional proteins such as occludin or claudin(s), hypoxia-induced enhancement of barrier function occurs through diverse pathways, ranging from increased mucin production [21] and molecules that modify mucins (e.g., intestinal trefoil factor) [17], to xenobiotic clearance (P-glycoprotein) [18] to nucleotide metabolism (ecto-5′-nucleotidase, CD73) [19][20] and nucleotide signaling (adenosine A2B receptor) [20] (Fig. 2).…”
Section: Hif Is Protective For Mucosal Inflammationmentioning
confidence: 99%
“…After 60 h, cells were stimulated with 1 g/ml of palmitoyl-3-cysteine-serine-lysine 4 (pam3CSK4) (Invivogen, San Diego, CA) for 15, 30, or 60 min or with tumor necrosis factor-␣ for 30 min (R & D Systems, Inc., Minneapolis, MN) as a positive control. Nuclear extracts were prepared according to a protocol previously reported (14). Briefly, cells were washed in 1 ml of ice-cold phosphate-buffered saline, collected by centrifugation (3000 rpm for 5 min at 4°C), and incubated in buffer A (10 mM HEPES, 1.5 mM MgCl 2 , 10 mM KCl, 0.1 mM EDTA, 0.1 mM EGTA, 1 mM dithiothreitol, 0.3 mM Na 3 VO 4 , protease inhibitor (complete Mini; Roche Applied Science)) for 10 min.…”
Section: Methodsmentioning
confidence: 99%